Dampak Game Online terhadap Pemerolehan Bahasa Kedua pada Anak (SATU Press Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2022)
Currently playing online games is one of the hobbies that is being carried out by all circles, including children. In addition to entertainment, online games are a means of learning for children to acquire foreign language vocabulary that they do not learn at school. This study aims to see the effect of online games on children's second language acquisition and to find out what factors influence this acquisition. The research method we use is a qualitative descriptive method with an observational approach. The subjects of our study were elementary school children aged 6 and 10 years. We conducted observations and interviews for one month so that we could find out how the influence of online games on second language acquisition in children aged 8 years and 11 years. The games played are Free fire, Mobile Legends, Minecraft, and Roblox. The results we get are that the children are familiar with new English vocabulary and know their meaning, the English vocabulary obtained is error, lag, battle, build, room, by one, cheat, shoot, and the other.